Study on work performance of the staff in Kuala Langat District Council and Tangkak District Council / Nur Aisyah Amid and Nur Zahirah Omar - Amid, Nur Aisyah; Omar, Nur Zahirah (Faculty of Administrative Science and Policy Studies, 2013)
This research emphasized on the purpose of conducting whether the staffs have fulfilling the attribute in Campbell theory such as Individual Different Perspective, Situational Perspective and Performance Regulation Perspective. The objective of this study were to measure the level of staff work performance, to measure the level of individual performance perspective, to measure the relationship between Individual Differences Perspective, Situational perspective, Performance Regulation Perspective and work performance and the last objective is to compare work performance between Kuala Langat District Council and Tangkak District Council. The data were collected by distributing the questionnaires to the 205 respondents from MDKL and 97 respondents from MDT. The descriptive analysis for Individual Differences Perspective was 4.08, Situational perspective was 4.16, Performance Regulation Perspective was 4.03 and Work Performance was 4.12. The correlation analysis of the data showed that Individual Difference Perspective (r= .981, Sig-value (p) = .000), Situational perspective (r= .975, Sig-value (p) = .000) and Performance Regulation Perspective (r= .979, Sig-value (p) = .000) were interrelated with the work performance of the staff. The Independent T-Test of the data showed that there is no significant differences exist – t (300) = -.359, p=0.720. To conclude the project research, the study had achieved the objectives which are to measure the relationship between Individual Differences Perspective, Situational perspective and Performance Regulation Perspective and work performance and also to compare the work performance between MDKL and MDT. This is because those attributes have a significant relationship towards work performance. Thus it gives the benefit of the MDKL and MDT in term of continuous learning, working in team, technology, and globalization and become proactively. The use of Balance Score Card as a tool to measure the work performances had help the researcher achieve the objective to measure the qprk performance of the staff in MDKL and MDT.